Respuesta :

Answer:

26

Step-by-step explanation:

For this case we must find the inverse of the following function:

[tex]y = x ^ 2-2[/tex]

We exchange the variables:

[tex]x = y ^ 2-2[/tex]

We clear the variable "y":

Adding 2 to both sides we have:

[tex]x + 2 = y ^ 2[/tex]

Applying square root on both sides of the equation:

[tex]y = \pm \sqrt {x + 2}[/tex]

We change y by [tex]f ^ {- 1} (x)[/tex]:[tex]f ^ {- 1} (x) =\pm \sqrt {x + 2}[/tex]

Answer:

[tex]f ^ {- 1} (x) = \pm\sqrt {x + 2}[/tex]